A Review On Human Communication Theory And Practice In Media Psychology - Vimala, Govindaraju (International Journal Documentation & Research Institute (IJDRI)., 2022)
Media psychology has emerged as a branch of psychology dealing with the interaction between media technology and people. Media psychology is a rapidly evolving field of journalism theory and practice dealing with the description of human behavior conditioned by exposure to the mass media. A study of individual and group media effects and core components of media culture that identify psychological patterns of human attitudes and behaviors in a multicultural media environment. Exploration of psychological phenomena and perceptual mechanisms of media texts. This article aims to provide an overview of the theory and practice of human communication in media psychology.